Chromosomal patterns of major and 5S ribosomal DNA in six icefish species (Perciformes, Notothenioidei, Channichthyidae) - F. MAZZEI; C. BONILLO; J. P. COUTANCEAU; C. OZOUF COSTAZ; GHIGLIOTTI, LAURA; PISANO, EVA (Springer, 2004)
Comparative chromosomal mapping of majorand 5S ribosomal genes in six species of the family Channichthyidae, namely Champsocephalus gunnari,Channichthys rhinoceratus, Chionodraco hamatus, Cryodraco atkinsoni, Pagetopsis macropterus and Neopagetopsisionah, was performed by fluorescence in-situhybridization, and using 28S and 5S ribosomal gene( rDNA) sequences as probes. Clusters of major and 5S ribosomal genes co-localize and likely compose the entire arm of a single pair of submetacentric chromosomes in all the species. In one species, P. macropterus, a second pair of chromosomes bears an additional common locus for both the two families of ribosomal genes. In all species, except N. ionah, additional copies of 5S rDNA sequences are also present on two other chromosome pairs, including the Y-chromosome in the males of Chionodraco hamatus. The pattern of ribosomal DNAs contributes to species-specific characterization in this fish family, and to our general knowledge and understanding of the chromosomal organization and evolution of the icefish genome